SEED GERMINATION OF ANACYCLUS PYRETHRUMD.C. IN EXPERIMENTAL FIELD - DIMRI, KIRAN; SHARMA, N.K. (The Scientific Temper, 2019)
The human society has been depending upon the forest resources for its sustenance, nourishment and keeping itself healthy, developing resistance to various ailments and the therapeutic uses. It is well said that good digestion regime is a boon to human race. The health and good digestion primarily depend upon the active and appropriate role of teeth. Tooth decay or carious teeth is one problem from which humans generally& mostlysuffer. Having developed most modern tooth pastes & tooth powders, including the use of the canalized tooth brushes, the teeth suffer from the problem of decaying, resulting in poor performance of food chewing, to disturb the digestion regime of human beings. There have been many claims to prevent tooth decay but for the want of the use of appropriate medicinal components in the tooth pastes & powders, this remains an acute problem. Anacyclus pyrethrum DC is one plant of Astraceae family, which possesses the property of arresting the tooth decay, carries, tooth ache & tonsillitis. Anacyclus pyrethrum DC is an exotic to India and has been introduced on a small scale in some southern parts of the country. In the present research investigations, experiments have been carried out to propagate this important exotic species in the sub- tropical, tropical and sub- temperate regions of the Garhwal Himalayas in Uttarakhand state. Seed germination is a prelude to the cultivation of the plant species and it affects the cost of production of plants in the case of rare & costly seeds.